All‐trans retinoic acid (ATRA) in non‐promyelocytic acute myeloid leukemia (AML): results of combination of ATRA with low‐dose Ara‐C in three elderly patients with NPM1‐mutated AML unfit for intensive chemotherapy and review of the literature. Issue 12 (24th October 2016) - Forghieri, Fabio; Bigliardi, Sara; Quadrelli, Chiara; Morselli, Monica; Potenza, Leonardo; Paolini, Ambra; Colaci, Elisabetta; Barozzi, Patrizia; Zucchini, Patrizia; Riva, Giovanni; Vallerini, Daniela; Lagreca, Ivana; et al.
Key Clinical Message: Based upon the clinical behavior of three patients, we suggest that the combination of low‐dose Ara‐C and all‐trans retinoic acid may potentially be effective in some elderly patients, unfit for intensive chemotherapy, affected with NPM1 ‐mutated acute myeloid leukemia without FLT3 mutations, warranting perspective clinical studies in these selected patients. Abstract : Based upon the clinical behavior of three patients, we suggest that the combination of low‐dose Ara‐C and all‐trans retinoic acid may potentially be effective in some elderly patients, unfit for intensive chemotherapy, affected with NPM1 ‐mutated acute myeloid leukemia without FLT3 mutations, warranting perspective clinical studies in these selected patients.